Drug effectiveness of 2nd and 3rd TNF inhibitors in psoriatic arthritis - Ørnbjerg, Lykke Midtbøll (2024)
Funding Information: This work was supported by Novartis. Novartis had no influence on the data collection, statistical analyses, manuscript preparation or decision to submit. Publisher Copyright: © 2024 The Authors